Deprivation and health in one general practice. - Marsh, G N (1986)
A detailed comparison made in late 1984 of 587 matched pairs of patients from neighbouring deprived and more endowed urban communities, both served by the same experienced primary health care team, showed much worse morbidity, with almost three times as much mental illness, in the deprived group. This group also had 60% more hospital admissions and 75% more casualty attendances. In contrast, they had a much lower uptake of preventive health care, especially childhood immunisations and cervical cytology in older women. A much higher birthrate within the deprived group, contributing to ill health by worsening overcrowding and deprivation, indicates that family planning is ineffective where it is most needed. Practical measures have now been instituted to improve the preventive care of the deprived community.